Iron Deficiency Anemia: The Utility of Upper Gastrointestinal Endoscopy and Histopathology - Al-Hamwandi, Adnan MH; Al-Dulaimi, Yaseen H; Al-Doori, Ali M; Al-Ani, Saad S; Al-Mashhdan, Azhar AJ (AL-Kindy College Medical Journal, 2007)
Background: occult blood loss must be considered as a possible cause in every case of iron deficiency anemia. Objective: to evaluate upper gastrointestinal endoscopy in finding a potential cause for iron deficiency anemia among children in Al-Anbar governorate. Methods: Twenty five children aged 2-14 years, referred to the gastroenterology unit in Al-Ramadi General Hospital for upper gastrointestinal endoscopy had iron deficiency anemia. Fiberoptic endoscopy was used under general anesthesia and endoscopic tissue biopsies were taken from 22 patients for histopathological examination. Results: The main presenting signs and symptoms were pallor, abdominal pain, and stunting. The upper gastrointestinal endoscopy showed thinning of duodenal folds & serrated mucosa in 8 (32%), duodenal ulcer in 3 (12%), esophageal varices in 1 (4%), nodular gastritis in 1 (4%), and reflux esophagitis in1 (4%), with a yield rate of 56%. While tissue biopsies revealed histopathological findings suggestive of celiac disease in 12 (48%), Giardia lamblia in 2 (8%), Helicobacter pylori gastritis in 1 (4%), and esophagitis in 1 (4%). There was a significant association between the endoscopic finding of thinning of duodenal folds and serrated mucosa and the histopathological finding suggestive of celiac disease, P<0.05. Conclusion: Iron deficiency anemia in children 2-14 years of age warrants upper gastrointestinal endoscopy to find potentially treatable causes for the iron deficiency anemia